Sino-African Relations and Western Misperceptions - MOUMOUNI, GUILLAUME (My University, 2007)
Sino-African relations are developing fast and seem to be all embracing. As one may expect, scholars from various horizons are showing greater interest in China-Africa links. Every year, quite a number of seminal works are devoted to these relations. The dyad “China-Africa” constitutes a new corpus both within Western academia and policy-making circles. It is no exaggeration to note that Sino-African relations are becoming a new field in international studies. The recent tour by President Hu Jintao of eight African countries, from January 30th to February 10th was an renewed occasion for extensive and intensive speculations among scholars and by the media. The concept of misperceptions, albeit central to international relations, is not much debated. Most of the time, it is linked to decision-making in warfare. But here, my focal point is the distorted reading of some Sino-African relationships by many Western observers. I therefore concentrate on three major issues: the overlooking of Africa’s domestic factors, the China’s “colonization” advocacy, and the questioning of Sino-African relations as being deeply entrenched. I argue that Western misperceptions are linked to colonial and Cold War legacies, the influence of Western NGOs, and a rising China that results in calls by the West for a defensive policy.
Keywords: Sino-African relations; Western misperceptions; colonial and Cold War legacies.